A influência do gênero na relação entre enriquecimento trabalho-família e comportamento de cidadania organizacional: um estudo com militares da força aérea brasileira - Rocha, Raquel Paiva Neves do Nascimento (2019)
This paper was developed with the objective of analyzing the influence of gender on the relationship between the Work Family Enrichment and the Behaviors of Organizational Citizenship. To do so, it conducted a descriptive research with a quantitative approach and opted to conduct a survey (Survey) on a sample of 255 military personnel, performed in Ala 4, guaranteed by the Brazilian Air Force located in the city of Santa Maria in the state of Rio Grande do Sul. One stage of data collection consisted of applying an online survey questionnaire divided into three parts: Sociodemographic and Professional Data; Work Family Enrichment Scale, validated by Gabardo-Martins, Ferreira and Valentini, (2016) and Organizational Citizenship Behaviors Scale, by Bastos, Siqueira and Gomes (2014). Quantitative data were used with the help of statistical software and analyzed using descriptive statistics, scale standardization and applied equation modeling (PLS-SEM). The results relevant to the sociodemographic profile of the sample show the predominance of male military personnel (84.31%), aged between 26 and 35 years (37.25%), married (67.45%), with higher education complete (29.41%) and no children (47.45%). The professional profile shows that most military personnel belong to aviation standards (26.28%), have 5-10 times lower income (40.39%), are a group of graduates - petty officer and sergeant - (45, 89 %), working time up to 5 years (51.76%) and workload of 31 to 40 hours per week (45.49%). In identifying aspects of Work Family Enrichment (WFE), it was found that 215 male military personnel, 109 (50.7%) had a moderate level of work family enrichment, while for family work enrichment 172 (80%) described high level. As for female participants, 20 (50%) had a high level of work family enrichment and 30 (75%) had a high level of enrichment in family work. Regarding the dimensions that involve the performances of organizational citizenship, both genders consider a high rate of creative suggestions (CS), such as taller women (82.5%) of dissemination of the organizational image (DOI) compared to men (68.8%) and 204 (94.9%) men and 38 (95%) women with high level of participation in colleagues (PC). In order to verify the weighting influence of gender in the relations between the dimensions, a structural model was adopted via partial selected equations. The results demonstrated that of the six suggested hypotheses, three were rejected. The hypothesis that gender weighs the relationship between WFE and DOI was accepted, but when analyzing this effect for the relationship between FWE and DOI with hypothesis was rejected. Note that gender has no weighting effect on the relationship between WFE and PC and also on the relationship between FWE and PC for a military sample. Finally, it was revealed that the relationships between WFE and CS and FWE and CS were weighting by gender.